Effect of Microcystis aeruginosa–Associated Microcystin‐LR on the Survival of 2 Life Stages of Freshwater Mussel (Lampsilis siliquoidea). (8th August 2019) - Gene, Samantha May; Shahmohamadloo, Rene Sahba; Ortiz, Xavier; Prosser, Ryan S.
Abstract: Microcystin‐LR is a toxin commonly produced by the cyanobacterium Microcystis aeruginosa. It is present in harmful algal blooms and is a concern for both human and environmental health in Canadian freshwater systems. Previous studies have investigated the toxicity of microcystin‐LR to other organisms such as fish; however, it is important to assess its toxicity to native freshwater mussels (family Unionidae), which are considered imperiled. The present study examined the toxicity of microcystin‐LR to fatmucket mussels ( Lampsilis siliquoidea ) at 2 different life stages. Juvenile mussels were exposed to microcystin‐LR in a 28‐d chronic test, and glochidia underwent a 72‐h acute toxicity test. There was no significant relationship between glochidia viability and microcystin‐LR concentration. The median lethal concentration (LC50) value for juvenile mussels after 28 d of exposure was 2.1 µg/L. To determine the environmental relevance of the observed toxicity, an environmental exposure distribution was created using Canadian and Canadian–US Great Lakes microcystin measurements. The 28‐d LC50 value (2.1 µg/L) was greater than those values that occurred in the environment 95% of the time; however, the LC10 (0.45 µg/L) and LC25 (0.97 μg/L) values were not greater than the measured microcystin environmental values. This finding indicates that microcystins may exert toxic effects on juvenile mussels at environmentally relevant concentrations. Further investigation should be considered in terms of prolonged exposure to persistent microcystin‐LR, and toxicity to sensitive species at different life stages. Environ Toxicol Chem 2019;38:2137–2144. © 2019 SETAC.